Cathodoluminescence analysis of nonmetallic inclusions of nitrides in steel. (2nd September 2018) - Imashuku, Susumu; Wagatsuma, Kazuaki
Abstract : Identification of nitride inclusions such as boron nitride (BN) and aluminum nitride (AlN) is important in the steelmaking industry because BN inclusions deteriorate the creep strength of ferritic heat‐resistant steel, and AlN inclusions cause transverse cracking in twin‐induced‐plasticity steel. The conventional method employed for the analysis of such inclusions in steel comprises both optical microscopy and electron probe microanalysis (EPMA), which is the time‐consuming. The aim of this study is to investigate the application of cathodoluminescence (CL) analysis (both images and spectra) to the rapid identification of BN and AlN inclusions. Measurement samples were prepared by heating mixtures of 99 mass% Fe and 1 mass% B or Al powders at 1550°C in a nitrogen atmosphere. BN inclusions larger than 5 μm and AlN inclusions 20 μm in size were identified within 1 second on the basis of their luminescence color (blue‐violet for BN and blue for AlN) in the CL images. We demonstrated that BN, AlN, and alumina inclusions could be identified from their CL spectra without the conventional method of EPMA. Capturing a CL image can provide a means of rapidly identifying BN and AlN inclusions in steel. We also carried out CL analysis on a sample containing TiN inclusions which can trigger cleavage fracture in low‐carbon steels. No luminescence was detected in the CL image, and there were no CL spectral peaks, indicating that it is difficult to apply CL analysis to the identification of TiN inclusions.